How Far for a Buck? Tax Differences and the Location of Retail Gasoline Activity in Southeast Chicagoland - Manuszak, Mark D; Moul, Charles C (The Review of Economics and Statistics, 2009)
We exploit variation in gasoline and cigarettes taxes in adjacent political jurisdictions for northern Illinois and Indiana to examine consumers' trade-off between prices and travel. We develop a model that relates activity in the retail gasoline industry around the tax borders to consumer locations. Our results indicate that the willingness of a typical Chicagoland consumer to travel an additional mile to buy gasoline corresponds to about $0.065 to $0.084 per gallon. According to our estimates, the observed area of Chicago, the jurisdiction with the highest taxes, is missing approximately 40% of the capacity that would exist were taxes equalized.